Association of abstinence time with semen quality in men who undergoing fertility evaluation: a cross-sectional study from 3052 participants - Yao, Guanying; Qi, Qinglin; Dou, Xianchao; Zhou, Wen; Bai, Shun; Zhang, Xi (Frontiers in Endocrinology, 2025)
ObjectiveAbstinence time has been associated with semen quality, but the results remain controversial.MethodsThis study recruited 3052 men undergoing fertility evaluation. Abstinence time (AT) was categorized as short (0-1 day), WHO-recommended (2-7 days) and long (>7 days). Semen parameters including volume, sperm concentration, progressive motility, total motility, total motility sperm count (TMSC), morphology and DNA fragmentation index were assessed for their association with AT.ResultsShort AT was significantly associated with lower semen volume (P< 0.001), sperm concentration (P= 0.01) and TMSC (P< 0.001), while long AT was significantly associated with higher sperm concentration (P= 0.006), reduced progressive motility (P= 0.005) and total motility (P= 0.02), and higher DFI (P< 0.001). Restricted cubic spline models demonstrated a non-linear relationship between AT and the risk of low semen volume (Pnon-linear < 0.001), sperm concentration (Pnon-linear = 0.039) and TMSC (Pnon-linear < 0.001).ConclusionsOur findings suggest both short and long AT were significantly associated with lower sperm quality, which indicated the importance of maintaining a recommended AT (2-7days) for semen analysis. Additionally, short abstinence periods may be recommended to maintain optimal sperm DNA integrity.